Comparative Analysis of Economic Development between Indonesia and South Korea: Institutional and Policy Perspectives - Muhammad Imam (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study compares the trajectory of economic development in Indonesia and South Korea from 1960 to 2018, two countries that shared similar starting points after gaining independence in 1945 and experiencing political upheaval during the 1960s. Despite these similarities, South Korea transformed into a highly industrialized and prosperous economy, while Indonesia lagged behind. Through historical and policy analysis, this paper identifies key factors contributing to this divergence, focusing on differences in economic policy orientation (inclusive vs. extractive institutions), urbanization and human capital development (education and health), and industrialization strategies. South Korea’s inclusive state-led industrial policy, investment in human capital, and effective urban planning under authoritarian rule created the foundation for rapid industrial growth, particularly through the development of chaebols. In contrast, Indonesia’s extractive economic structure, reliance on oil and commodity exports, and weak governance contributed to slower growth and persistent developmental challenges. This comparative analysis concludes that institutional quality, policy coherence, and strategic prioritization of industrial and human development are critical drivers of sustained economic transformation.